A bibliometric analysis of sustainable development research in higher education institutions (HEIs): key trends, global collaborations and influential contributions (2015–2023) - Mohamed Ali Osman; Abdirahman Ahmed Sheikh Farah; Abdirahman Ibrahim Abdi (Cogent Education)
This study presents a bibliometric analysis of sustainable development (SD) research in higher education institutions (HEIs) from 2015 to 2023, analyzing 1,122 articles using VOS viewer. Findings reveal a significant rise in publications, from 105 in 2019 to 263 in 2023, reflecting growing academic focus on sustainability in HEIs. The UK emerged as the most prolific contributor, with 5,450 citations, underscoring its scholarly impact. Citation trends peaked at 3,745 in 2019 but declined thereafter. International collaborations and leading Q1 journals highlighted the field’s global engagement and research quality. The analysis emphasizes a rapidly expanding body of research, driven by contributions from select countries. Limitations include restricted database sources and the need for broader publication avenues. The study concludes with recommendations for HEIs to strengthen sustainability initiatives through curricular integration of SD concepts, faculty development, cross-institutional partnerships, and policy reforms to institutionalize sustainable practices. These insights offer a comprehensive overview of current research trends, guiding strategies to enhance HEIs’ role in advancing sustainability. The findings affirm the field’s academic rigor while identifying areas for future exploration, such as expanding data sources and fostering interdisciplinary research. The study emphasises HEIs' vital role in sustainable development and suggests measures to boost their influence.